2014
DOI: 10.1111/jace.13047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Piezoelectric Properties and Phase Coexistence in (Ba,Ca)(Ti,Zr)O3 Ceramics

Abstract: High piezoelectric properties are desired for lead‐free piezoelectric materials in consideration as a replacement for lead‐based materials in applications. Due to the high piezoelectric coefficient, (Ba100−xCax) (Ti100−yZry) O3 (BCTZ) piezoelectric ceramics have been considered as a promising lead‐free alternate piezoelectric material. Here, six compositions were selected based on a prediction that all the compositions would have high piezoelectric coefficient at room temperature. The results confirmed all com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 32 publications
0
37
1
Order By: Relevance
“…However, because there is strong coupling between lattice distortions (strain) and the ferroelectric order parameter (polarization), it is inevitable that there will be changes in elastic and anelastic properties associated with the discrete phase transitions in the BZT-xBCT lead-free system. [34][35][36] The real part of the elastic response to a dynamic stress field, expressed as the storage modulus (E 0 ), is the inverse of the mechanical susceptibility. The imaginary part of the response is the loss modulus (E 00 ).…”
mentioning
confidence: 99%
“…However, because there is strong coupling between lattice distortions (strain) and the ferroelectric order parameter (polarization), it is inevitable that there will be changes in elastic and anelastic properties associated with the discrete phase transitions in the BZT-xBCT lead-free system. [34][35][36] The real part of the elastic response to a dynamic stress field, expressed as the storage modulus (E 0 ), is the inverse of the mechanical susceptibility. The imaginary part of the response is the loss modulus (E 00 ).…”
mentioning
confidence: 99%
“…The temperature decay of is enlarged after crossing the various phase boundaries, in agreement with previous works. 194,305 This is expected considering that excursions across PPBs diminish the poling state of ferroelectrics. 150 Literature reports have indicated that generally the properties of the R phase are much more susceptible to temperature and poling treatments.…”
Section: Temperature-and Frequency-dependent Dielectric Propertiesmentioning
confidence: 88%
“…194,320,325 Electromechanical properties were found to have local maxima values around phase boundaries, followed by diminished properties. 194,305 Higher temperature stability was generally observed away from phase boundaries, although with diminished magnitudes. 317 At room temperature it was demonstrated that 4 kV/mm lead to saturation of the poling degree given by angle.…”
Section: Electromechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zhang et al obtained a piezoelectric constant d 33 as high as 200 pC/N by introducing Zr 4+ dopant in (Ca, Ba) TiO 3 [21]. Zhang et al reported (Ba, Ca) (Ti, Zr) O 3 (abbreviated as BCTZ) ceramics which have high piezolelectric and ferroelectric properties [22]. Liu et al reported a BCTZ ceramic which has a high piezoelectric constant d 33 (~620 pC/N) [23].…”
Section: Introductionmentioning
confidence: 99%